1.5 vs 3 Tesla Magnetic Resonance Imaging: A Review of Favorite Clinical Applications for Both Field Strengths—Part 2. Issue 11 (November 2021) - Radbruch, Alexander; Paech, Daniel; Gassenmaier, Sebastian; Luetkens, Julian; Isaak, Alexander; Herrmann, Judith; Othman, Ahmed; Schäfer, Jürgen; Nikolaou, Konstantin
Abstract : Abstract: The second part of this review deals with experiences in neuroradiological and pediatric examinations using modern magnetic resonance imaging systems with 1.5 T and 3 T, with special attention paid to experiences in pediatric cardiac imaging. In addition, whole-body examinations, which are widely used for diagnostic purposes in systemic diseases, are compared with respect to the image quality obtained in different body parts at both field strengths. A systematic overview of the technical differences at 1.5 T and 3 T has been presented in part 1 of this review, as well as several organ-based magnetic resonance imaging applications including musculoskeletal imaging, abdominal imaging, and prostate diagnostics.